ADAPTIVE CODE-SWITCHING IN INTERNATIONAL CLASSROOMS: SCAFFOLDING, ENGAGEMENT, AND INCLUSIVITY - Maflukha Maflukha; Nirwanto Maruf; Dwita Laksmita Rachmawati (University of Kuningan, 2025)
This study investigates teacher-student code-switching practices in English language instruction within international class programs in Indonesian high schools. Employing a mixed-methods approach, it combines quantitative classroom observations with qualitative interviews to explore patterns, frequency, and pedagogical functions of code-switching. Quantitative findings show that inter-sentential code-switching is the most frequent type, accounting for 48% of occurrences, followed by intra-sentential (38%) and tag-switching (14%). Code-switching frequency varies significantly with students' English proficiency levels (p < 0.001), with lower proficiency groups experiencing more frequent switches, averaging 8.5 instances per lesson during complex topic introductions. Teachers strategically employ code-switching to scaffold understanding, clarify abstract concepts, manage classrooms, and accommodate diverse linguistic backgrounds. Qualitative data reveal that both teachers and students perceive code-switching as crucial for lowering anxiety, enhancing comprehension, and increasing active participation. While students benefit from the alternate use of English and Indonesian to build confidence, they tend to prefer English-dominant instruction for greater immersion. This study advances code-switching theory by incorporating social and affective dimensions in multilingual pedagogy and underscores the need for flexible language policies that recognize code-switching as a valid instructional tool. The findings advocate for bilingual strategies in teacher training and educational policy to improve English learning outcomes in diverse international classroom settings.